Animated Video Learning Media Oriented to the Tri Kona Concept on the Life Cycle of Living Things for The Fourth Grade of Elementary School - Septyani, Ni Kadek Sary; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Universitas Pendidikan Ganesha, 2023)
The low ability of students to understand science subject matter is because, in the learning process, the teacher is less able to utilize the use of media that suits the needs of students. So the purpose of this research is to develop Tri Kona concept-oriented animated video learning media on the life cycle of living things and for class IV student learning that has been tested for validity, practicality, and student responses. This research belongs to the type of development research, which was developed using the ADDIE model, with five research stages, namely the analysis, design, development, implementation, and evaluation stages. The subjects involved in this study were 4 lecturers as experts, 1 teacher and 12 students. Meanwhile, the research object is the design, content validity and practicality of the Tri Kona concept-oriented animation video learning media on the life cycle of living things being developed. Collecting data, this study was carried out using the questionnaire method with the instrument used to collect data, namely a questionnaire. The data obtained in the study were then analyzed using qualitative and quantitative descriptive analysis techniques. The research analysis results showed that the Tri Kona concept-oriented animation video learning media on the life cycle of living things was declared valid. The practicality percentage was 98.75%, and the percentage of student responses for individual and small group trials was 94.17% and 96.11%. Based on these results, the Tri Kona concept-oriented animated video learning media on the life cycle of living things is appropriate for learning.